The effect of iron oxide nanoparticles on Bacillus subtilis biofilm, growth and viability. (November 2017) - Ranmadugala, Dinali; Ebrahiminezhad, Alireza; Manley-Harris, Merilyn; Ghasemi, Younes; Berenjian, Aydin
Graphical abstract: Highlights: Naked and 3-aminopropyltriethoxy silane coated IONs (APTES@IONs) were successfully prepared and characterised. APTES@IONs found to be effective in reducing biofilm biomass without affecting the grwoth and cell viability of B. subtilis . Naked IONs significantly affected the viability of B. subtilis without significant reduction in biofilm biomass. Abstract: Bacillus subtilis is one of the key microorganisms for the industrial production of many value added products. The fermentation of this bacterium is associated with biofilm formation that results in major process and operational issues. The study of the effect of magnetic nanoparticles on the bacterial cells can immensely contribute to designing intensified bioprocess methods Present study was aimed at understanding the effect of superparamagnetic iron oxide (naked IONs) and 3-aminopropyltriethoxy silane coated IONs (IONs@APTES) on biofilm formation, growth and viability of Bacillus subtilis. Both IONs were successfully prepared and characterised by transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction patterns (XRD) and vibrating sample magnetometry (VSM). IONs@APTES at 100 μg/mL were found to significantly reduce the total biofilm biomass without affecting the cell viability compared with the behavior of naked IONS, which significantly affected the viability of B. subtilis at high concentrations without any significant redution in biofilm biomass. This suggests an active role of IONs@APTES in eliminating the biofilm formation as compared to the naked IONs. This work suggests the possibility of using IONs@APTES coated bacteria for a range of applications for future industrial fermentation with Bacillus subtilis .